Analyzing the Students' Needs of an Academic Reading Class at a Private University in Lubuklinggau - Fiani, Ani; Fadillah, Julia Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This present paper studied the studentsâ€™ demands of a reading class at a private institution in Lubuklinggau, South Sumatera. The needs are separated into two elements, namely studentsâ€™ needs and wants. This research was a descriptive study employing a qualitative method with the data collection strategy using the mix of the closed-ended and open-ended questionnaires. The respondents in this study were 27 students from 2021 at English Education Study Program of Universitas PGRI Silampari who had taken academic reading subject. They were given 25 closed-ended questions and three open-ended questions. The results showed that 88.14% of the students agreed that the topic variation in an academic reading class was importance, the Importance of Tasks in Academic Reading was categorized as â€œimportantâ€ (81%), Topic for academic was categorized as â€œimportantâ€ (63.5%). There were 86.19% students expected to have the improvement in the term of topics in Academic Reading Materials. There were 74% students wanted the improvement in the aspect of tasks. Then, 56% of 27 students wanted the improvement in term of skills. In conclusion, the students agreed that the topic should be realistic, relevant, and diverse. Moreover, in consideration of the needs of the pupils, the topic should be diversified, engaging, and current. Key word: Academic Reading, Needs Analysis, University Students